Reading Comprehension Questions in Second Grade of Senior High School English Text Book “Look Ahead” by Erlangga - Reni Mustika Ningsih (Magister Scientiae, 2009)
This study analyzed the reading comprehension question of the English text book published by Erlangga “Look Ahead”. The analysis is based on the Cognitive Domain of Bloom’s Taxonomy. There are 6 categories of Bloom’s Taxonomy namely knowledge, comprehension, application, analysis, synthesis, and evaluation. The study reveals that there are 221 reading comprehension questions. Among these questions are 30.32 % knowledge questions, 8.15 % comprehension questions, 8.10 % application questions, 23.98 % analysis questions. 4.52 % synthesis questions, 14.93 % evaluation questions.